Assessing the Travel Health Knowledge of Australian Pharmacists - Ian M. Heslop (Pharmacy, 2020)
Worldwide, the numbers of travellers are increasing, with pharmacists having the potential to play a significant role in the provision of pre-travel health services to a large number of these travellers. However, studies examining whether pharmacists have the travel health knowledge to provide these services are limited. This study thus aimed to explore the travel health knowledge of Australian pharmacists. Surveys assessing pharmacists’ knowledge of travel health were distributed through the Pharmaceutical Society of Australia and community pharmacies for self-completion. Overall, the travel health knowledge of participants was found to be good. However, although the majority of participants were aware of the common causes of morbidity and mortality in travel health, some slightly overestimated the prevalence of malaria and were less knowledgeable about the global distribution of some diseases. Most participants also demonstrated an ability to give appropriate advice on the management of traveller’s diarhoea, the selection of appropriate items for inclusion in travel first aid kits, vaccinations, and malarial chemoprophylaxis for travellers visiting endemic areas. This study highlights that Australian pharmacists have the knowledge to deliver travel health advice, with the potential to improve both access and outcomes for travellers.